The portrayal of local and the international cultures in the Sudanese English Language Syllabus (Spine) (Global Journal of Human-Social Science, 2011)
This paper explores issues related to the portrayal of the local culture as well as international culture in the English Language materials used in Sudanese schools The researcher then intends to venture into a thorough evaluation of the elements of different cultures in SPINE syllabus Sudan Practical Integrated national English series book 1to6 This study employs a set of checklist which has been used as a guideline to analyze the cultural aspects in a curriculum in order to examine English Language textbooks used in schools in Sudan The findings show that there was insufficient incorporation of cultural aspects into the English materials Many of the available cultural elements were presented at a superficial level and not discussed within the holistic cultural experience The findings suggest that the absence and the lack of certain cultural aspects in the materials may be due to the fact some cultural topics are avoided fearing sensitivity and that they may be implicitly portrayed through for example value integration moral and educational emphasis This study recommends that language learning materials must be able to present the language learners own culture and all the cultures that surround them and the materials must be useful and effective both as English learning materials as well as a tool for promoting cultural knowledge and understanding among Sudanese students
Keywords: Multiculturalism; syllabus design; local and international culture